Analisis Economic Order Quantity (EOQ) Pada Usaha Pengolahan Kopi “Oen Kopi” di Kota Banda Aceh - Kurniawan, Putra; Tanjung, Yulia Windi; Fuqara, Fantashir Awwal; Darmansyah, Dedy (Universitas Teuku Umar, 2025)
The procurement of raw materials is a crucial aspect for companies producing goods, as it significantly impacts the continuity of business operations. However, challenges often arise in ensuring the availability of raw materials that are timely, of good quality, and in the right quantities, as experienced by the OEN Coffee Processing Business. This study aims to analyze the Economic Order Quantity (EOQ) in the “OEN Kopi” Coffee Processing Business in Banda Aceh City. Using a quantitative descriptive approach, data was collected through in-depth interviews, focus group discussions (FGD), and observations. The results show that the application of the EOQ method to the inventory of coffee beans, sugar, sweetened condensed milk, and UHT milk brought significant changes. Both ordering and storage costs decreased drastically, resulting in a much lower total inventory cost after implementing EOQ. The savings achieved reached 98.3% for coffee beans, 98.4% for sugar, 98.1% for sweetened condensed milk, and 98.6% for UHT milk. This efficiency allows the company to allocate resources more effectively and increase profits. Thus, the EOQ method not only optimizes inventory management but also contributes to improved business profitability.